Virus-Induced Maternal Immune Activation as an Environmental Factor in the Etiology of Autism and Schizophrenia - Aïcha Massrali; Dwaipayan Adhya; Deepak P. Srivastava; Simon Baron‐Cohen; Mark Kotter (2022)
Maternal immune activation (MIA) is mediated by activation of inflammatory pathways resulting in increased levels of cytokines and chemokines that cross the placental and blood-brain barriers altering fetal neural development. Maternal viral infection is one of the most well-known causes for immune activation in pregnant women. MIA and immune abnormalities are key players in the etiology of developmental conditions such as autism, schizophrenia, ADHD, and depression. Experimental evidence implicating MIA in with different effects in the offspring is complex. For decades, scientists have relied on either MIA models or human epidemiological data or a combination of both. MIA models are generated using infection/pathogenic agents to induce an immunological reaction in rodents and monitor the effects. Human epidemiological studies investigate a link between maternal infection and/or high levels of cytokines in pregnant mothers and the likelihood of developing conditions. In this review, we discuss the importance of understanding the relationship between virus-mediated MIA and neurodevelopmental conditions, focusing on autism and schizophrenia. We further discuss the different methods of studying MIA and their limitations and focus on the different factors contributing to MIA heterogeneity.